Experimental study on the thermal effects in shear-driven liquid film evaporation under dynamic boundary conditions - Wenping Xu; Rui Su; Ning Xu; Ying Zhang; Wenyu Chen; Xiaodong Ruan; Xin Fu (AIP Advances)
In semiconductor manufacturing processes, under shear conditions, deionized water tends to retain a liquid film on the wafer surface due to interfacial interactions. This phenomenon arises from the dynamic balance between shear-induced fluid motion and adhesion forces at the solid–liquid interface, significantly increasing the likelihood of liquid film retention. The residual liquid film fragments into microdroplets while undergoing evaporation, and the cooling effect induced by this evaporation generates a temperature gradient on the silicon wafer surface. In this paper, we focus on the control of the evaporation of the residual liquid film and droplets by experimental study. By reviewing the existing theoretical models of evaporation and conducting an analytical recognition of the influencing factors, the critical variables of the experimental design was identified. Evaporation power was used to describe the speed of evaporation, and a specialized device for measuring this power was designed through computational fluid dynamic (CFD) simulation using the industry-standard computational software ANSYS. The experimental study of evaporation power was carried out by introducing an orthogonal experiment to determine the factors affecting evaporation power. It was found that the influence on evaporation power follows the sequence, θSE > Vs > Qas > Has > h. Notably, the contact angle exerts an extremely significant impact, followed by the wafer velocity, while the flow rate of air for the sweeping liquid film shows less significance. Moreover, increasing the hydrophobicity of the wafer surface can obtain a larger critical moving speed because it reduces the likelihood of droplet leakage and film pulling, reducing the generation of residual liquid and the corresponding cooling effect due to evaporation.